Conservation of the Tomb of Anen - Pinch-Brock, Lyla
Located on necropolis of the West Bank of Luxor, the tomb of Anen belonged to an ancient Egyptian priest who served under the reign of Amenhotep III. Over time, the tomb had deteriorated and the roof caved in, filling the tomb with rubble and subjecting the wall paintings to light, heat, and water damage, as well as looters. This project, sponsored by the Royal Ontario Museum, was to conserve and protect the tomb of Anen (TT120), as well as the paintings inside.